EDUKASI PENCEGAHAN PENYEBARAN BERITA HOAKS MELALUI SOSIAL MEDIA DI SMK NEGERI 71 JAKARTA - Rabiatul Adawiyah; Kurniawan Kurniawan; Febry Amirullah; Elvara Norma Aroyandini (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
The development of information technology has resulted in negative impacts, one of which is hoax news that spreads quickly through social media. Students of SMK N 71 Jakarta use social media every day, both for online learning and personal purposes, such as communicating with family and friends. This situation makes students vulnerable to receiving hoax news. Therefore, this community service was carried out to provide students education in socialization and training. The implementation of the education was attended by class X students from the Department of Software Engineering, Visual Communication Design, and Animation, where each major was taken two, so the total number of students who took part in this activity was six classes or around 50 students. The results of this community service are that there has been socialization with material on the meaning of hoax news, the characteristics of hoax news, distinguishing between a hoax and non-hoax news, examples of hoax news found on social media, and the critical role of students in helping prevent the spread of hoax news. The presenters also conducted training through demonstrations on how students can recognize hoax news from the title and content of the news, how students can check the truth of a news story, and how students can report if they find news that is indicated as a hoax which is practiced directly by students. This service activity ends by giving assignments to students to monitor social media and report if there is news that is indicated as a hoax, then provide information to presenters and teachers. The results of these community service activities are that students gain comprehensive knowledge about hoax news; students can practice how to recognize hoax news so that students can distinguish between news that contains hoaxes and those that do not, and students can check the truth of news and can report if there is news that is indicated to contain hoaxes. Perkembangan teknologi informasi mengakibatkan munculnya dampak negatif, salah satunya yaitu adanya berita hoaks yang tersebar dengan mudah melalui sosial media. Siswa SMK N 71 Jakarta merupakan siswa yang setiap hari menggunakan sosial media, baik untuk keperluan pembelajaran daring maupun untuk keperluan pribadi, seperti untuk berkomunikasi dengan keluarga dan teman. Hal tersebut menjadikan siswa rawan untuk menerima berita hoaks. Maka dari itu dilakukanlah pengabdian masyarakat ini dengan tujuan untuk memberikan edukasi berupa sosialisasi dan pelatihan kepada siswa. Pelaksanaan edukasi diikuti oleh siswa kelas X dari jurusan Rekayasa Perangkat Lunak, Desain Komunikasi Visual, dan Animasi, dimana masing-masing jurusan diambil dua, sehingga total siswa yang mengikuti kegiatan ini adalah sebanyak enam kelas atau sekitar 50 siswa. Hasil pengabdian masyarakat ini yaitu telah dilakukan sosialisasi dengan materi pengertian berita hoaks, ciri-ciri berita hoaks, membedakan antara berita hoaks dan bukan hoaks, contoh-contoh berita hoaks yang ditemukan di media sosial, serta pentingnya peranan siswa dalam membantu mencegah oenyebaran berita hoaks. Pemateri juga melakukan pelatihan melalui demonstrasi tentang bagaimana siswa dapat mengenali berita hoaks dari judul maupun isi berita, bagaimana siswa dapat mengecek kebenaran suatu berita, serta bagaimana siswa dapat melakukan pelaporan jika menemukan berita yang terindikasi hoaks yang dipraktikkan secara langsung oleh siswa. Kegiatan pengabdian ini diakhiri dengan memberikan tugas kepada siswa untuk memantau sosial media dan melaporkan jika terdapat berita yang terindikasi hoaks, kemudian memberikan informasi kepada pemateri maupun guru.